2003
DOI: 10.2109/jcersj.111.811
|View full text |Cite
|
Sign up to set email alerts
|

Dispersibility of BaTiO3 Aqueous Slurries with Poly Ammonium Acrylate Based Dispersant

Abstract: Ùaeªaeç_ïÞÇ¡ÜnªUÜpC^BaTiO 3 nµåaeômªU« â{ ÂEªTqÞ E]êME½ìÁêÞThe dispersibility of aqueous BaTiO 3 slurries with poly ammonium acrylatebased dispersant has been inves tigated. BaTiO 3 particles were welldispersed in the high pH region and the adsorption behavior of disper sant strongly depended on the slurry pH. The dispersion of BaTiO 3 particles at various pH was also elucidat ed by characterizing the sedimentation density, viscosity of slurries, amount of adsorbed dispersant and tapecasted green sheets. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In addition, Sakamoto et al (2003) has shown that at high pH region, the BaTiO 3 particles were stable. Moreover, the density of this solution should be higher than that of oil (to be beneath the oil layer) and lower than that of the sol to allow the drop of sol to pass through the oil-ammonia solution interface.…”
Section: Fig 2 -Raman Spectra Of the Titanium Precursor (A) Acetic mentioning
confidence: 99%
“…In addition, Sakamoto et al (2003) has shown that at high pH region, the BaTiO 3 particles were stable. Moreover, the density of this solution should be higher than that of oil (to be beneath the oil layer) and lower than that of the sol to allow the drop of sol to pass through the oil-ammonia solution interface.…”
Section: Fig 2 -Raman Spectra Of the Titanium Precursor (A) Acetic mentioning
confidence: 99%
“…Moreover, some works relate that dielectric properties are promoted by use of dispersant [12,13]. The concentrated ammonia is necessary to avoid the carbonation of barium ions, since it was demonstrated that at a mild basic Scheme 1 Synthesis and the two ways to shape forming BaTiO 3 compounds Scheme 2 Assembling description of a non-thermal plasma laboratory reactor pH, BaCO 3 compound could be formed [14,15], whereas for highly concentrated ammonia solutions, this formation is inhibited. Moreover, the density of this solution should be higher than that of oil (to be beneath the oil layer) and lower than that of the sol to allow the drop of sol to pass through the oil-ammonia solution interface.…”
Section: Resultsmentioning
confidence: 99%
“…50) Therefore, well-dispersed powders in water were prepared by carefully selecting the dispersant and adjusting pH towards the alkaline region such that Ba 2+ dissolution and stoichiometry change were successfully eliminated. 51) Lead-containing compounds, as cited by the Environmental Protection Agency (EPA) of the US, is one of the top 17 chemicals posing the greatest threat to human beings and the environment. 52) Lead oxide is one of the main constituents of well-known piezoelectric ceramics such as Pb(Zr,Ti)O3, Pb(Mg1/3Nb2/3)O3-PbTiO3, Pb(Zn1/3Nb2/3)O3-PbTiO3.…”
Section: Organic and Inorganic Substances With Low Toxicity Or Non-toxicmentioning
confidence: 99%